KELAYAKAN MEDIA CERGAM DALAM SUBMATERI ZAT MAKANAN DI KELAS XI SMA - Hosniah, Hosniah; Candramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility of illustrated story (cergam) as a medium of learning in Sub Material of Food Substances in second grade of high school. This was a descriptive study and the data collection was carried out using validation instruments. Feasibility assessment was carried out by 5 validators consisting of 2 lecturers of Biology Education Study Program FKIP Tanjungpura University Pontianak and 3 biology teachers in SMAN 01 Siantan, SMA Taman Mulia Kubu Raya and SMAN 01 Sungai Raya. The feasibility analysis showed that the pictorial story was valid with the total score of validity of 3.6, therefore the pictorial story was declared feasible to be used as a learning medium in Sub Material of Food Substances in second grade of high school.Â Keywords:Â Feasibility, Pictorial Story, Sub Material of Food SubstancesÂ